Cancer stem cell–immune cell crosstalk in breast tumor microenvironment: a determinant of therapeutic facet - Guha, Aishwarya; Goswami, Kuntal Kanti; Sultana, Jasmine; Ganguly, Nilanjan; Choudhury, Pritha Roy; Chakravarti, Mohona; Bhuniya, Avishek; Sarkar, Anirban; Bera, Saurav; Dhar, Sukanya; Das, Juhina; Das, Tapasi; et al. (Frontiers in Immunology, 2023)
Breast cancer (BC) is globally one of the leading killers amongst women. Within breast tumor, a minor population of transformed cells which are accountable for drug resistance, survival and metastasis, are known as breast cancer stem cells (BCSCs). Several experimental evidences have indicated that BCSCs influence the functionality of immune cells. They evade immune-surveillance by altering characteristics of immune cells and modulate tumor landscape to immune suppressive type. They are proficient in switching from quiescent phase (slowly cycling) to actively proliferating phenotype with high-degree of plasticity. This review confers the relevance and impact of crosstalk between immune cells and BCSCs as fate determinant for BC prognosis. It also focuses on current strategies of targeting these aberrant BCSCs that could open avenues for treatment of breast carcinoma.